2015
DOI: 10.1080/15381501.2013.859113
|View full text |Cite
|
Sign up to set email alerts
|

HIV Status Disclosure and Condom Use Among HIV-Positive Men Who Have Sex With Men andHijras(Male-to-Female Transgender People) in India: Implications for Prevention

Abstract: This mixed-methods investigation combines a quantitative survey, focus groups, and in-depth interviews to examine sexual risk behaviors and HIV status disclosure among HIV-positive hijras (male-to-female transgender people) and HIV-positive men who have sex with men (MSM) in Chennai and Mumbai, India. From the survey results, the authors found a relatively high prevalence of inconsistent condom use for anal sex with male partners-about one-fifth to almost one-half, depending on the type of partner (regular, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…(9, 10) For example, a study conducted in India revealed that only about one-quarter of Indian MSM disclosed their HIV status to their male partners. (11) Lack of HIV serostatus disclosure among MSM in LMICs may be due to fear of discrimination and violence(12), lack of social and psychological support(13, 14), and low HIV testing rate. (15) For example, due to feared discrimination and social isolation, and feared relationship broken-up, people in LMICs are less likely to disclose their serostatus to partners.…”
Section: Introductionmentioning
confidence: 99%
“…(9, 10) For example, a study conducted in India revealed that only about one-quarter of Indian MSM disclosed their HIV status to their male partners. (11) Lack of HIV serostatus disclosure among MSM in LMICs may be due to fear of discrimination and violence(12), lack of social and psychological support(13, 14), and low HIV testing rate. (15) For example, due to feared discrimination and social isolation, and feared relationship broken-up, people in LMICs are less likely to disclose their serostatus to partners.…”
Section: Introductionmentioning
confidence: 99%
“…An invisible and often ignored population due to stigma and societal expectations, male sex workers (MSW) who have sex with men are at elevated risk for HIV and other STIs compared to the broader MSM population. Contextual factors related to sex work, including stigma, increased financial incentives for riskier behaviors, and lack of access to prevention services make it likely that the prevalence of HIV and STIs among MSW exceeds that of the broader MSM population in India (Biello, Colby, Closson, & Mimiaga, 2014; Chakrapani, Shunmugam, Newman, Kershaw, & Dubrow, 2015; Closson et al, 2015; Oldenburg, Biello, et al, 2014; Oldenburg et al, 2015; Shinde, Setia, Row-Kavi, Anand, & Jerajani, 2009). Few studies have sought to estimate the prevalence of HIV among MSW specifically, with some estimates as high as 33.0% among a population of MSW living in Maharashtra (Shinde et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Indian TGW engage in condomless sex with male regular partners to show love, trust, and intimacy (Chakrapani et al 2007), and also because of fear of being rejected (Chakrapani et al 2015). This context may be unique to the moderate victimization profile and is consistent with research on the difficulty of negotiating safer sex between TGW and their partners (Kosenko 2011b).…”
Section: Discussionmentioning
confidence: 59%
“…It might have been anticipated that TGW in the high victimization profile would have a heightened likelihood of all five sexual risk outcomes, but this was not supported in our findings. The high victimization profile had the highest prevalence of TGW living with HIV and previous research finds that people living with HIV, who are aware of their HIV status, are more willing to adapt safer sex behaviors (Chakrapani et al 2015). Moreover, these findings may be indicative of desensitization theories.…”
Section: Discussionmentioning
confidence: 76%